Indonesian Adaptation of the Multicultural School Counseling Behavior Scale - Rifani, Endang; Artika, Munik Yuni; Kunwijaya, Indrajati; Hani, Haris Yuftika (Jurnal Kajian Bimbingan dan Konseling, 2021)
School counselors should possess multicultural competence as an important aspect in the implementation of guidance and counseling services. Counseling services require school counselors to empower students who have different cultural backgrounds from theirs. The Multicultural School Counseling Behavior Scale (MSCBS) is a scale to measure the school counselors’ multicultural competence represented by their attitudes and behavior in implementing guidance and counseling services in schools. This study aims to adapt the MSCBS into Indonesian, considering the limited multicultural competency measuring tool for school counselors that includes the attitudes and behavior of school counselors in counseling. The research subjects were 257 junior and senior high school counselors. The scale test was carried out through a readability test involving small groups and a quantitative test using Confirmatory Factor Analysis (CFA) to examine the validity of the scale and generate a fit model showing a satisfactory construct validity and acceptable indices of the goodness of fit. The Alpha Cronbach test was conducted to examine scale reliability. The test results show great reliability. The results show that the Indonesian version of MSCBS with 29 items can be employed for guidance and counseling research purposes.